Fotografia documentaria e modernismo “transatlantico”: influenze europee e americane in Changing New York di Berenice Abbott - Frongia, Antonello (Rivista di studi di fotografia. Journal of Studies in Photography, 2016)
One of the most significant photo-books of the 1930s, Berenice Abbott’s Changing New York has increasingly been understood as a critical study of the American metropolis modelled on Atget’s survey of Old Paris. This essay relies on the notion of “transatlantic modernism” to uncover the influence of European as well as American visual culture on Abbott’s work, suggesting a dialectical exchange between documentary and modernist art in her visual language and selection of subjects.